Curves of AW(k)-type in 3-dimensional null cone - Kulahci, Mihriban; Bektas, Mehmet; Erguet, Mahmut (Elsevier Science Bv, 2007)
In this Letter, we investigate curves of AW(k)-type (1 <= k <= 3) in the 3-dimensional null cone and we give curvature conditions of these kind of curves. (c) 2007 Elsevier BN. All rights reserved.
Keywords: null cone; frenet formulas; AW(k)-type curve